PELAKSANAAN PEMBANGUNAN PARTISIPATIF DI KELURAHAN MAKROMAN KECAMATAN SAMARINDA ILIR - SALASIAH SALASIAH (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
In the current era of regional autonomy, the concept of development should be implemented in every region in Indonesia is development that involves the public in any process. The process is meant in this case, ie not only at the planning stage, but also at the stage of development project implementation, monitoring and evaluation stages of development results. With the issuance of regulations by the government to support the concept, it is expected to generate development in accordance with the needs of society as well as the construction of object subject development practitioners.With the implementation of research Makroman Sub Samarinda, Samarinda Ilir. This is expected to provide an overview of how community participation in the implementation of regional development so that the concept of participatory development that has been applied to measuring and can be used as a reference in future studies related to the substance of the discussion.From the research that has been carried out, it can be illustrated that the application of participatory development in the Village Makroman if musrenbang refer to the results that have been recorded on BAPPEDA of Samarinda, the results obtained are in the planning stages, although people still participate, but at this stage of the implementation of community participation expected No not at all because it was found by the implementation phase of the project carried out by the contractor winning bidder. However, if we refer to the development projects undertaken by the three empowerment program that runs in the Village Makroman, primarily by PNPM Mandiri Village in the study found that people's enthusiasm to participate in every stage of development that started in the planning, implementation, until the evaluation phase the project is very high. It can be concluded in the implementation phase are still many things that must be addressed.